Multiple Neuroendocrine Tumors in Stomach and Duodenum in a Multiple Endocrine Neoplasia Type 1 Patient - Kim, Bohyun; Yang, Han-Kwang; Kim, Woo Ho (Journal of pathology and translational medicine, 2018)
A 67-year-old woman with a history of subtotal parathyroidectomy, distal pancreatectomy, and total splenectomy 23 years prior underwent surgical gastric resection for neuroendocrine tumors of the stomach and duodenum. Meticulous examination of the entire stomach and duodenum revealed multiple scattered, minute neuroendocrine tumors. To the best of our knowledge, this is the first case report of a patient diagnosed with gastroduodenal neuroendocrine tumors associated with multiple endocrine neoplasia type 1 (MEN 1) in whom complete histologic mapping of the whole gastrectomy specimen was performed. The presence of MEN 1-associated neuroendocrine tumors in the stomach is very rare, but should be considered in patients diagnosed with MEN 1 who present with a new tumor in the stomach.